Distribution pattern of corticolous lichens in different areas of Kathmandu valley, Nepal - Karmacharya, Neena; Upreti, Dalip K; Chettri, Mukesh K. (Banko Janakari, 2022)
This study attempts to document the lichen species and their distribution in different areas of Kathmandu valley, Nepal. Twenty sampling sites with different degrees of air pollution categorized as disturbed (industrial, heavy traffic and residential areas) and undisturbed areas (clean area) were selected for the study. Sampling was done using the quadrat method. To enumerate the total number of lichen species found in Kathmandu valley, lichen specimens were collected from inside as well as outside the quadrats. A total of 97 species of corticolous lichens belonging to 21 families and 44 genera were recorded from the study sites. Parmeliaceae was the largest family followed by Graphidaceae. The importance value analysis showed that Candelaria concolor (115.2), Dirinaria aegialita, Lepraria sp., Phaeophyscia hispidula var. hispidula and Physcia sorediosa (106.02) are the most common and dominant lichen species in Kathmandu valley. Among the most common and dominant lichen species, Candelaria concolor, Dirinaria aegialita, Phaeophyscia hispidula var. hispidula and Physcia sorediosa were found concentrated in heavy traffic areas whereas Lepraria sp. in the industrial areas. A higher number of lichen species (70%) was recorded in undisturbed areas than in disturbed areas (50%). These study confirm that the distribution of lichen flora is strongly influenced by degrees of pollution. This in turn suggests that lichens can be used as bio indicators of air quality in the Kathmandu valley.